Abnormal gray and white matter volume in delusional infestation - Wolf, Robert Christian; Depping, Malte S.; Thomann, Philipp (Progress in neuro-psychopharmacology & biological psychiatry, 2013)
Little is known about the neural basis of delusional infestation (DI), the delusional belief to be infested with pathogens. Case series and the response to anti-dopaminergic medication indicate disruptions in dopaminergic neurotransmission in the striatum (caudate, putamen), but did not allow for population-based inference. Here, we report the first whole-brain structural neuroimaging study to investigate gray and white matter abnormalities in DI compared to controls. In this study, we used structural magnetic resonance imaging and voxel-based morphometry to investigate gray and white matter volume in 16 DI patients and 16 matched healthy controls. Lower gray matter volume in DI patients compared to controls was found in left medial, lateral and right superior frontal cortices, left anterior cingulate cortex, bilateral insula, left thalamus, right striatal areas and in lateral and medial temporal cortical regions (p<0.05, cluster-corrected). Higher white matter volume in DI patients compared to controls was found in right middle cingulate, left frontal opercular and bilateral striatal regions (p<0.05, cluster-corrected). This study shows that structural changes in prefrontal, temporal, insular, cingulate and striatal brain regions are associated with DI, supporting a neurobiological model of disrupted prefrontal control over somato-sensory representations.